Psychopharmacotherapy of Depressive Disorders in Alcoholism - Khayatov Rustam Batirbekovich; Velilyaeva Alie Sabrievna; Kurbanov Anvar Alamovich (Genius Journals, 2022)
According to various authors, the prevalence of depression in patients with alcoholism varies from 28 to 60%, which is 2-3 times more than in the general population. The risk of committing suicide averages 17.7%, while in the general population suicide attempts are made by about 4%. Full-scale depression that meets the criteria for a major depressive episode occurs in approximately 10% of patients with alcoholism, subdepression at the level of dysthymia - in 30% of patients. Depression in patients with alcoholism in most cases of somatogenic origin, i.e. associated with the toxic effect of alcohol on the central nervous system (CNS), and in most patients it spontaneously decreases within 2-4 weeks after the relief of alcohol withdrawal syndrome and abstinence from ethanol. A rational combination of psychopharmacotherapy and psychotherapy improves the prognosis of comorbid pathology
Keywords: Depressive Disorders; Alcohol Addiction; Comorbidity